Pengaruh Pengeluaran Pemerintah Bidang Bantuan Sosial dan Kesehatan, Konsumsi Rumah Tangga dan Pendidikan Terhadap Indeks Pembangunan Manusia di Indonesia - Yosi Tamara; Yeniwati Yeniwati (Universitas Negeri Padang, 2020)
This study explains the effect of government spending on social and health assistance on HDI, household consumption of HDI and education about HDI in Indonesia. This study combines cross-sectional data in 33 provinces with a time series from 2014-2018, with the Regression Panel method with Effective Effect model selection tests. The results showed that: (1) Government expenditure on social assistance has a positive and not significant effect on the human development index in Indonesia, (2) Government expenditure on health has a positive and significant effect on the human development index in Indonesia (3) House consumption the ladder has a positive and significant effect on the human development index in Indonesia, (4) Education has a positive and significant effect on the human development index in Indonesia.